Passive voice, first person pronouns and mental process verbs in the physical sciences reseach article - David Banks (Revista de Lingüística y Lenguas Aplicadas, 2021)
Recent studies have suggested that there has been a decrease in passive use, and an increase in the use of first person pronouns in scientific writing. This study looks at six sample texts from the physical sciences. The correlation between low passive use and use of first person pronoun subjects is only partial. The influx of verbs of a mathematical nature in recent decades has led to an increase in verbs of mental process. These lend themselves more easily to the use of first person pronouns. There are now two models available, a progressive model using fewer passives and a number of first person pronoun subjects, and a traditional model using passive forms extensively and avoiding first person pronoun subjects.